1979
DOI: 10.1063/1.1135698
|View full text |Cite
|
Sign up to set email alerts
|

Production of reproducible Rayleigh–Taylor instabilities

Abstract: A device is described that excites individual modes of the standing wave spectrum for surface waves on water in a water tank of rectangular cross section. By synchronizing the downward acceleration of the tank with the standing wave on the water, Rayleigh-Taylor instabilities with reproducible characteristics are excited at the air-water interface. By controlling the width of the tank, the fluid motion is made to be largely two dimensional. The reproducibility of the phenomenon and the two-dimensional characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Experiments on the RT instability were performed by, among others, Lewis [18], Duff et al [19], and Popil and Curzon [20]. Lewis [18], who studied the RT instability created by imposing a pressure difference across a column of water, concluded that the instability could be divided into three stages: (1) an initial stage characterized by an exponential increase in the amplitude of the interfacial waves, (2) a transition stage that includes the formation of ''mushrooms'' of air that start to penetrate into the liquid, and (3) a final stage where spikes of air penetrate the liquid at a uniform velocity that scales with the square root of the gravitational acceleration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experiments on the RT instability were performed by, among others, Lewis [18], Duff et al [19], and Popil and Curzon [20]. Lewis [18], who studied the RT instability created by imposing a pressure difference across a column of water, concluded that the instability could be divided into three stages: (1) an initial stage characterized by an exponential increase in the amplitude of the interfacial waves, (2) a transition stage that includes the formation of ''mushrooms'' of air that start to penetrate into the liquid, and (3) a final stage where spikes of air penetrate the liquid at a uniform velocity that scales with the square root of the gravitational acceleration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, majority of the experiments described above (Cole & Tankin 1973;Emmons et al 1960;Ratafia 1973) used a vibrating paddle for generating the initial perturbations which resulted in generation of a wide spectrum of modes instead of a single eigenmode (Popil & Curzon 1979). The phase of such modes and their amplitudes were variable and thus, the experiments were not repeatable.…”
Section: Psecondsmentioning
confidence: 99%
“…The phase of such modes and their amplitudes were variable and thus, the experiments were not repeatable. Popil and Curzon (1979) used a electrostatic generator to accurately generate single-mod …”
Section: Psecondsmentioning
confidence: 99%
“…They obtained an approximate single-mode perturbation at the density interface by oscillating a paddle, and measured the growth of individual bubbles and spikes using high-speed photography. Other researchers have also used some type of accelerated tank containing miscible or immiscible fluids of different densities to investigate the growth of Rayleigh-Taylor instability-driven mixing layers (Ratafia 1973;Cole & Tankin 1973;Popil & Curzon 1979;Read 1984;Jacobs & Catton 1988;Kucherenko et al 1994Kucherenko et al , 1997Kucherenko et al , 2003aDimonte & Schneider 1996, Dimonte 1999Wilkinson 2004).…”
Section: Previous Experimental Investigations Of Rayleigh-taylor Instmentioning
confidence: 99%
“…Some experiments imposed an approximate sinusoidal perturbation at the two-fluid interface and primarily used ordinary photographic techniques to measure the growth of individual bubbles and spikes (Ratafia 1973;Cole & Tankin 1973;Popil & Curzon 1979;Jacobs & Catton 1988;Wilkinson 2004). In addition to the measurement of the mixing layer width, Wilkinson (2004) used planar laser-induced fluorescence (PLIF) to measure the growth and internal structure of the single-mode, three-dimensional Rayleigh-Taylor instability.…”
Section: Previous Experimental Investigations Of Rayleigh-taylor Instmentioning
confidence: 99%